2013
DOI: 10.1002/ejic.201300283
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Formation of cis‐ and trans‐Di[(3‐chloropropyl)isopropoxysilyl]‐Bridged Double‐Decker Octaphenylsilsesquioxanes

Abstract: Silsesquioxane formation competing with the deprotonation of alcohol solvents in the presence of a strong base to form alkoxides is reported for the first time. Evidently, sodium isopropoxide is formed during the synthesis of the sodium salt of a double‐decker octaphenylsilsesquioxane tetrasilanolate in 2‐propanol as the solvent, which leads to the formation of unexpected cis‐ and trans‐di[(3‐chloropropyl)isopropoxysilyl]‐bridged double‐decker octaphenylsilsesquioxanes after in situ coupling with 3‐chloropropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…After drying under reduced pressure, recrystallization in the mixed solvent of chloroform and 2‐propanol (1:1) afforded colorless crystals in a 40 % yield of 3 . For the synthesis of 4 , the dichlorooctamethyltetrasiloxane linkage was expected to react intermolecularly rather than intramolecularly to yield polymeric materials . Surprisingly, though the reaction provided polymer linkages forming a long siloxane chain, the closed cage structure 4 was obtained in only slightly lower yield as compared to 2 and 3 .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…After drying under reduced pressure, recrystallization in the mixed solvent of chloroform and 2‐propanol (1:1) afforded colorless crystals in a 40 % yield of 3 . For the synthesis of 4 , the dichlorooctamethyltetrasiloxane linkage was expected to react intermolecularly rather than intramolecularly to yield polymeric materials . Surprisingly, though the reaction provided polymer linkages forming a long siloxane chain, the closed cage structure 4 was obtained in only slightly lower yield as compared to 2 and 3 .…”
Section: Methodsmentioning
confidence: 97%
“…The doubly‐extended butterfly cage T 8 D 4 3 , T 8 D 6 4 , and T 8 D 8 5 , both ends of which are linked to oligosiloxane chains, were synthesized in 91 %, 86 %, 64 %, respectively by the reaction of DDSQ‐tetraol 1 a with methyl substituted oligosiloxane in the presence of triethylamine (Scheme ). Tetraol 1 a can be prepared in high yield from DDSQ‐(ONa) 4 1 b that was easily synthesized from trimethoxyphenylsilane in 2‐propanol via hydrolytic condensation using sodium hydroxide and refluxing for 4 h followed by stirring for 15 h at 20 °C according to a previously reported method . The condensation reactions between tetraol 1 a and dichlorooligosiloxanes are somewhat slow, requiring a reaction time of 14 h at room temperature and several hours at reflux.…”
Section: Methodsmentioning
confidence: 99%
“…Dichlorodisiloxane 1 [37] was freshly prepared by the hydrolytic condensation of dichlorodiphenylsilane in the presence of water for 3 h. The product obtained after distillation was a viscous colorless oil in 35% yield. The synthesis procedure for DDSQ-ONa ( 2 ) is described in detail in previous reports [19,21,38]. A 2-propanol solution of trimethoxyphenylsilane with NaOH and water was refluxed for 4 h, followed by continuous stirring at room temperature for 15 h. After filtration, a white solid was obtained in 58% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these compounds find a wide range of applications in polymers [8,9,10,11], sensors [12], catalysis [7,8,9,13], organic light-emitting diodes [14], host-guest complexes [15,16], and porous materials [17]. Most of the double-decker silsesquioxanes (DDSQ) [10,11,14,18,19,20,21,22,23,24,25,26] and polyhedral oligomeric silsesquioxanes [7,8,9,12,13,15,16,17,27,28,29] have a symmetrical structure with the same organic functional group on both sides. In contrast, only a few studies on unsymmetrical silsesquioxane or siloxane cages have been reported because of the difficulty in obtaining a perfect Janus structure via a simple hydrolytic condensation of two organomonosilane precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The cell parameters were retrieved by using the SMART software and refined with SAINT for all observed reflections. [32,33] The crystal structures were solved by direct methods by using SHELXS-97 and refined on F 2 by full-matrix least-squares procedures with SHELXL-97. [34] Hydrogen atoms were placed at calculated positions and included as riding atoms.…”
Section: X-ray Structural Determinationmentioning
confidence: 99%